Ответ:
Пошаговое объяснение:
![\left \{ {{3x-8y=18} \atop {-3x+4y=-6}} \right. \left \{ {{3x-8y=18} \atop {-3x+4y=-6}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B3x-8y%3D18%7D%20%5Catop%20%7B-3x%2B4y%3D-6%7D%7D%20%5Cright.)
методом сложения
-4у = 12
у = 12 : (-4)
у = -3
3х - 8 * (-3) = 18
3х + 24 = 18
3х = 18 - 24
3х = -6
х = - 6 : 3
х = -2
![\left \{ {{3x-3y=12} \atop {3x+2y=17}} \right. \left \{ {{3x-3y=12} \atop {3x+2y=17}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B3x-3y%3D12%7D%20%5Catop%20%7B3x%2B2y%3D17%7D%7D%20%5Cright.)
первое уравнение умножить на -1 будет
![\left \{ {{-3x+3y=-12} \atop {3x+2y=17} \right. \left \{ {{-3x+3y=-12} \atop {3x+2y=17} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7B-3x%2B3y%3D-12%7D%20%5Catop%20%7B3x%2B2y%3D17%7D%20%5Cright.)
5у = 5
у = 5 : 5
у = 1
3х - 3 * 1 = 12
3х = 12 + 3
3х = 15
х = 15 : 3
х = 5